THE MEANING OF HIJAB IN RELIGIOUS BEHAVIOR AMONG THE PEOPLE OF TANJUNG MAKMUR VILLAGE, NORTH LABUHANBATU DISTRICT - Br Simbolon, Rinasari; Yulia, Fatma (Pena Cendekia Insani, 2025)
This study examines the meaning of the hijab in religious behavior among the people of Tanjung Makmur Village, North Labuhanbatu Regency. The hijab is no longer seen solely as a religious obligation but has evolved into a symbol of religious identity, social status, and fashion, with varying interpretations among Muslim women in the village. Some wear it out of faith, while others follow social, cultural, or environmental pressures. This research uses a qualitative method with a phenomenological approach to explore the subjective experiences of informants regarding the hijab’s significance in their religious lives. Data was collected through in-depth interviews, observation, and documentation with six informants, including Muslim women who wear the hijab and a local religious figure. The results revealed that the hijab represents obedience to Allah, self-identity, protection from negative views, and a form of da'wah. Influencing factors include family, religious education, personal awareness, and religious norms. The study concludes that wearing the hijab is closely linked to positive religious behavior.